HISTORICAL GENESIS OF BECOMING OF TERRITORIAL SAMOORGANIZACII OF POPULATION ON WALKS OF LIFE OF UKRAINE - Ткаченко, В.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The formation of the territorial organization of population on the territory of Ukraine. Characterized seven stages of the territorial organization of population on the territory of Ukraine: рolis model, model of princely epoch, мagdeburg  legal model, model of Cossack self-government, externally-іmperial model, the people's Republican, etat  model.  It is examined different forms of self-ogranization of population as a display of mentality.